PHILOSOPHICAL APPRAISAL OF THE PROBLEM OF FACEBOOK COMMUNITY STANDARDS VIS-A-VIS S.L ANDERSON & M. ANDERSON PROBLEMS OF MACHINE ETHICS - Jecinta C Nwobi; Chinedu Ifeakor (dialektika kontemporer, 2023)
The twenty-first century world is increasingly being populated by autonomous artificial machines equipped with sophisticated artificial intelligence (AI) technologies. Facebook in 2018 made a breakthrough with the introduction of some ethically modeled policies known as the Facebook Community Standards. Facebook Community Standards can be described as an Artificial Moral Agent whose policy rationale is to create a safe space for users by prohibiting contents that contradict some universal moral standards. This paper using the research methodology of analysis attempts to identify the ethical problem (s) surrounding the enforcement of Facebook Community Standards and evaluate the identified problem (s) vis a vis M. Anderson and S.L Andersons’ postulations on problems facing the development of machine ethics. M. Anderson & S.L Anderson postulated that the major issues facing the development of machine ethics is the question about the possibility or impossibility of computing ethics into machines posed by ethical issues of moral relativism, moral universalism, ethical emotivism, moral consciousness among others. Akin these ethical issues, this work observed that the users of Facebook are unjustly punished and segregated by the non-relative nature of the Community Standards to their individual moral and social values. Recommending as a solution to this problem, the research proposed the inclusion of the relativism to the enforcement of the community standards, that is, the universalism of the standards enforcement globally should take into view the reality of non-uniformity of ethical and moral values.